Lb3.260 Multidrug resistant mycoplasma genitalium in hiv-infected men who have sex with men (MSM) in the united states. (8th July 2017) - Geisler, Li Xiao; William M; Waites, Ken B; Aaron, Kristal J; Dionne-Odom, Jodie A
Abstract : Introduction: Mycoplasma genitalium (MG) is a common cause of urethritis in men. In the U.S., CDC recommends treatment for MG with azithromycin or moxifloxacin, but treatment success is threatened by increasing resistance to both therapies. Rectal MG infection has been described among MSM, but little is known about rectal MG prevalence and frequency of antibiotic-resistant MG in HIV-infected MSM. Methods: We retrospectively evaluated the prevalence of MG infection and antibiotic-resistant MG in 158 HIV-infected MSM who self-collected rectal and urine samples for a study at an HIV clinic in Birmingham, Alabama in 2014–2016. Eligibility criteria included receptive anal intercourse in the past 30 days and no recent antibiotic exposure (except trimethoprim-sulfamethoxazole). A real-time PCR assay was used to detect MG and macrolide resistance by targeting the 23S rRNA gene. Nested PCRs were used to detect mutations in quinolone resistant determination regions in gyrA, gyrB, parC and parE genes. Results: MG infection was detected in 27 MSM (17.1%); 18 (11.4%) at the genital site and 9 (5.7%) at the rectal site. The bacterial load ranged from 2–32, 700 genome copies/µl. Macrolide resistant MG was detected in 19 men (70.4%), featuring typical 23S rRNA mutations (A2071G or A2072G transitions). One subject with MG had novel gene mutations (G1972T and G2038T) with unknown function. Eight (29.6%) had fluoroquinolone-resistant MG harbouring parC mutations that cause changes in amino acid position 83 (S83I or S83R); 4 of them had an additional P62S mutation in parC and 1 had a F475S mutation in gyrB . Five men (18.5%) had MG with dual macrolide and fluoroquinolone resistance. The prevalence of resistance was similar at rectal and genital sites. Conclusion: This is the first U.S. study to document a high frequency of macrolide and fluoroquinolone-resistant MG in HIV-infected MSM at rectal and genital sites. If these resistance mutations are associated with clinical treatment failure, more effective options to treat MG are needed.